Experiences of women of colour who were third culture kids or internationally mobile youth : an exploratory study of implications for global leadership development : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Manawatū, New Zealand - Chatiya Nantham, Rhema Roja (Massey University, 2023)
Global leadership development programmes (GLDPs) are typically focussed on competency development and teaching culturally appropriate etiquette, but, adapting to new contexts often involves challenges to people’s sense of self, addressing an area which is known as identity work. Learning from people who encountered such challenges early in life could assist in developing global leaders by offering insights into the kinds of identity work strategies needed to deal with their offshore posting, and to ensure that identity work processes are designed into such programmes. To address these aims, this study draws on the lived experiences of nine women of colour who lived outside their home country as children or adolescents, a cohort known as Third Culture Kids (TCKs), to identify various identity-related issues they encountered and the lessons these experiences offer for global leadership development. As such, this interdisciplinary study draws on and contributes to literatures related to TCKs and Adult TCKs (ATCKs), global leadership development, and identity work for leadership development. This qualitative study comprised a series of workshops designed specifically to foster identity work amongst the participants. The data was collected via virtual focus group discussions. The study adopted a combination of participatory and emancipatory action research approaches, underpinned by a social constructionist epistemology and is theoretically informed by Critical Race Feminism, anti-racist feminisms, and identity theory as key influences. These decisions reflect the aim of centring attention on a cohort routinely understudied in the TCK, global leadership development and leadership development literatures, namely women of colour. The findings were thematically analysed via an inductive approach to identify the experiences and identity work strategies of participants as TCKs in response to the racist-sexist prejudices they encountered, their implicit leadership theories and their approach to leadership, showing how the focus group process was itself a vehicle for doing identity work in relationship to their leader identities. I identify the lessons that can be drawn from TCKs, and from the methods used in this study, to inform the deployment of identity work in GLDPs. From these findings, I develop frameworks explaining the identity work processes experienced by TCKs and how they internalised their leadership identity via the methods used in my study and build models for GLDPs from these insights.
Keywords: Leadership; Executives; Training of; International business enterprises; Personnel management; Identity (Psychology); Women immigrants; Minority women; Psychology; 350707 Leadership